2022
DOI: 10.1111/ajsp.12551
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐like spokesperson for campaigning an anti‐plastic straw movement to young adults: Is it effective?

Abstract: Parental communication is still relatively meaningful in Asian families with hierarchical, vertical, and authoritative relationships. Meanwhile, children's pro-environmental behaviour in emerging Asian nations tends to be passive, leading to a need for intervention from the closest parties, often the parent, whose familial role in green communication has not been examined. This study uses social learning theory to examine the interplay of parent-like spokespeople and message appeals in affecting young adults' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 142 publications
0
2
0
Order By: Relevance
“…This illogical pattern was related to the idea of "satisfaction inertia," according to which customers prefer to continue with tried-and-true products that continuously satisfy their wants and expectations, even when more environmentally friendly alternatives are available (Wang et al, 2019). Furthermore, Suci et al, (2022) did an experimental study and found that participants' intentions to convert to eco-friendly alternatives considerably dropped when they were very satisfied with their present items. Despite being aware of eco-friendly options, switching intentions may be resisted due to cognitive dissonance resulting from the desire to uphold a positive selfconcept as an environmentally responsible person (Bardin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This illogical pattern was related to the idea of "satisfaction inertia," according to which customers prefer to continue with tried-and-true products that continuously satisfy their wants and expectations, even when more environmentally friendly alternatives are available (Wang et al, 2019). Furthermore, Suci et al, (2022) did an experimental study and found that participants' intentions to convert to eco-friendly alternatives considerably dropped when they were very satisfied with their present items. Despite being aware of eco-friendly options, switching intentions may be resisted due to cognitive dissonance resulting from the desire to uphold a positive selfconcept as an environmentally responsible person (Bardin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consumer preferences for eco-friendly items have undergone a paradigm shift across all countries as a result of growing environmental concerns and the pressing need to stop climate change. These ecofriendly decisions indicate a growing understanding of how consumer behavior affects the environment and a willingness among consumers to change their buying habits to more sustainable ones (Suci et al, 2022). The internet has completely changed how consumers obtain information and make decisions regarding sustainable consumerism and eco-friendly products.…”
Section: Introductionmentioning
confidence: 99%